Beyond the visual and verbal: Using participant-produced photographs in research on the surroundings for care at the end-of-life. (November 2016) - Tishelman, Carol; Lindqvist, Olav; Hajdarevic, Senada; Rasmussen, Birgit H.; Goliath, Ida
Abstract: The web of relationships between wellbeing and the environments in which people live has long been recognized. However, relatively little research has been conducted about end-of-life surroundings from the perspective of the dying person. In this study, we investigate which aspects of their surroundings are particularly meaningful for the people inhabiting them in the last phases of life, based on participant-produced photographs with follow-up interviews. Twenty-three people were purposefully recruited via specialized in-patient palliative care/hospice units, specialized palliative care home care teams, and residential care facilities for the elderly. Participants were given a digital camera, and asked to take pictures of that which was meaningful for them in their surroundings. The interviewer later viewed the photographs with the participant, asking: "what is this picture of?" and "why is it meaningful to you?" The database consists of 76 photographs with follow-up interviews, which were analyzed qualitatively in an iterative process. These empirical data demonstrate how a sense of being valued, and of being able to maintain contacts with one's daily life and sense of identity appear supported or hindered by features of the care surroundings. These features include a positive aesthetic experience incorporating both sensory stimulation using one's body as well as general ambiance; support appropriate for maintaining a sense of functional independence; and connections with one's past, present and future as a person within a wider world. Corporeality appears crucial for understanding, negotiating and interacting in one's surroundings, while maintaining both physical and social function. This data collection approach was found to offer alternative forms of expression as verbal ability decreases and symptom burden increases, making it useful in end-of-life research and practice development. Highlights: Interactions with EoL surroundings create an "aesthetic of care" in various ways. Surroundings support or hinder feeling connection to daily life, identity and value. Physical, social and intellectual function appear intrinsic to aesthetics of care. Self-determination and minimal professional dependency seem to be aesthetic values. Participant-generated photographs were found beneficial for use in EoL research.